The modified Dmax method is reliable to predict the second ventilatory threshold in elite cross-country skiers - Fabre, N.; Balestreri, F.; Pellegrini, B.; Schena, F. (The Journal of Strength and Conditioning Research, 2010)
This study was designed to evaluate, in elite cross-country skiers, the capacity of the DMAX lactate threshold method and its modified version (DMAX MOD) to accurately predict the second ventilatory threshold (VT2). Twenty-three elite cross-country skiers carried out an incremental roller-ski test on a motorized treadmill. Ventilation, heart rate (HR), and gas exchanges were continuously recorded during the test. Blood was sampled at the end of each 3-minute work stage for lactate concentration measurements. The VT2 was individually determined by visual analysis. The DMAX, DMAX MOD points also with the 4 mmol/L fixed lactate concentration value (4 mM) were determined by a computerized program. Paired t tests showed nonsignificant differences between HR at VT2 and HR at DMAX MOD, between HR at VT2 and HR at 4 mM, and between HR at DMAX MOD and HR at 4 mM. HR at DMAX was significantly lower than HR at VT2, DMAX MOD, and at 4 mM (p < 0.001). HR at VT2 was strongly correlated with HR at 4 mM (r = 0.93, p < 0.001), HR at DMAX (r = 0.97, p < 0.001) and especially with HR at DMAX MOD (r = 0.99, p < 0.001). Bland-Altman plots showed that HR at DMAX underestimated HR at VT2 and permitted to observe that the DMAX method and particularly the DMAX MOD method had smaller limits of agreement as compared with the 4 mM method. Our results showed that the DMAX MOD lactate threshold measurement is extremely accurate to predict VT2 in elite cross-country skiers.